2013
DOI: 10.1149/2.083308jes
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Potential Cycling on PEMFC Durability

Abstract: Voltage cycling is one of the most damaging stressors for automotive PEMFC. Understanding of the effects of voltage cycling on performance degradation is crucial to improve PEMFC durability for automotive applications. This study focuses on the interaction between upper potential limit (UPL) and lower potential limit (LPL) on the stability of PEMFC. A well-defined peak of degradation rate is observed when the LPL is ∼0.8 V with UPL of 1.35 V. A mathematical model was developed to understand the observed relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 21 publications
3
39
0
Order By: Relevance
“…The multi-branched structure can prevent the aggregation of PtNi alloy nanourchins. Furthermore, it has been proved that the rod morphology does not undergo significant ripening [57][58][59][60][61]. Therefore, we believe that the loss of ESA on the PtNi alloy nanourchins could be largely attributed to the electrochemical dissolution.…”
Section: Electrochemical Performancementioning
confidence: 85%
See 1 more Smart Citation
“…The multi-branched structure can prevent the aggregation of PtNi alloy nanourchins. Furthermore, it has been proved that the rod morphology does not undergo significant ripening [57][58][59][60][61]. Therefore, we believe that the loss of ESA on the PtNi alloy nanourchins could be largely attributed to the electrochemical dissolution.…”
Section: Electrochemical Performancementioning
confidence: 85%
“…However, the dissolution of PtNi alloy nanourchins should be significantly suppressed, because the PtNi alloy nanourchins have higher onset potential for Pt oxidation in Fig. 4A, which contributes positively to less dissolution of Pt via the oxidation state [61]. …”
Section: Electrochemical Performancementioning
confidence: 99%
“…The particle size dependence of Pt dissolution has been attributed to the Gibbs-Thomson effect which induces an effectively higher potential on smaller particles as compared to larger ones and a Pt dissolution equilibrium and rate which increase with increasing anodic potential above 0.7 V. [10,11,20,28,38]. [27,54] Re-deposition will occur when metallic sites are present on the particle surfaces [53] and when the concentration of dissolved Pt surrounding the particles is higher than the equilibrium dissolved Pt concentration, which is a function of Pt particle size. [55] The extent of GSA loss for the experiments in this study can be interpreted in the context of the proposed mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…There are several modeling efforts of Pt electrocatalyst ECA loss in MEAs induced by various potential cycling protocols and temperatures. The Pt dissolution rates utilized in the modeling efforts of Darling and Meyers, [51] Bi et al, [52] and Zhang et al [53] are shown in Table 2. The cycling conditions which effect Pt dissolution rates were different in these efforts and differ from what were used in this study, but in general the rates range from 1 x 10 -10 to 2 x 10 -9 g/cm 2 -cycle.…”
Section: Overall Losses After 1000 Cyclesmentioning
confidence: 99%
“…The dominant decay mechanisms are Pt dissolution with or without redeposition [26][27][28][29][30][31][32], migration/ coalescence [33], catalyst nanoparticle size distribution change [34,35], and detachment from the support due to carbon corrosion [36]. The factors influencing the transient potential profiles include transition rates, the upper and lower potential limits (range between 0.6 and 1.0 V), and time at either idle (∼1.0 V) or peak (∼0.6 V) power [37]. The transition rates allow for the extent to oxide formation and reduction that control surface reorganization [25].…”
Section: Introductionmentioning
confidence: 99%